FUZZY LOGIC CONTROL APPLIED TO A PHOTOVOLTAIC SYSTEM CONNECTED TO CITY NETWORK FOR RESIDENTIAL USE - Lamas, W. Q.; Tani, H. M.; Reis, L. O. M.; Ribeiro, A. C. (Revista de Engenharia Térmica, 2008)
A simplified topology using power electronics and fuzzy logic control techniques for developing a photovoltaic generation system, at a low cost, to be used in residential systems, connected to the local distribution grid is herein proposed. A technique for determining maximum power points on photovoltaic panels, in order to transfer the powerful generated to the load, is studied, so to impart a minimum energy loss in the whole system. In the fuzzy logic controller development the relevant functions to the input and output photovoltaic system variables and the rules to be used in this controller is established and obtained from other photovoltaic systems, adapted to the system. Simulation results are obtained always focusing maximum power search by a fuzzy logic controller, through intelligent changes into control variables that will carry the work cycle of increasing converter and the inverter bridge. It is shown that while exists solar radiation variation and low voltage available on photovoltaic module, the increasing converter will supply necessary voltage to the inverter bridge operation.